The Wind-Induced Vibration Response of Modular High-Rise Buildings - Moore, Hollie (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2025)
Structural engineering continues to advance and push boundaries enabling taller, more slender and flexible structures to be realised. However, these structures are often more susceptible to significant wind-induced vibrations resulting in a dynamic response which can cause human discomfort. The inherent properties of a structure such as the mass, stiffness and damping ratio are the parameters which have the largest impact on its dynamic response. Quantifying these properties is essential in the design process of tall buildings in order to ensure habitability requirements are satisfied. Volumetric modular construction is a relatively new form of construction in which prefabricated room sized units are constructed in a factory environment and transported to a construction site to be positioned and stacked to create a finished building. Traditionally modular construction has been employed in low to medium rise repetitive structures. However, more recently, this form of construction has been applied in tall structures exceeding 160 m. At present, limited research is available on the inherent properties of modular structures, with no reported estimates of the damping ratio or stiffness of this form of construction available. This research aims to provide an initial insight into the wind-induced dynamic performance of high-rise modular buildings, develop data-informed surrogate models and to investigate suitable mitigation measures. The acceleration responses of two of the world’s tallest volumetric structures, Ten Degrees and College Road, located in Croydon, London, United Kingdom obtained from full-scale in situ monitoring were studied. OMA techniques have been used to identify the natural frequencies of the structures and to calculate initial estimates of the damping ratios. The identified natural frequencies were used alongside a stepped-beam numerical model to quantify the bending stiffness of the volumetric module - RC core structural system. Using the identified inherent properties, a data-informed MDOF surrogate model of a modular building was developed and calibrated using the results from the in situ monitoring. This MDOF surrogate model was found to reflect the dynamic response of the case study structures better than FE models. Parametric assessment of the response control of MVDTLDs was performed using the MDOF surrogate model, alongside an equivalent TMD model of a TLD. MVDTLDs offer a suitable control strategy which can be optimised to suit the form of modular buildings. Hybrid tests using a full-scale TLD and the MDOF surrogate model were also performed, incorporating results from full-scale tests of modular buildings with full-scale testing of control strategies and enabling parametric assessment which would otherwise not be feasible. Both the numerical and experimental results show that multiple distributed TLDs can effectively decrease the wind-induced response of modular buildings, providing an opportunistic control measure capable of ensuring habitability requirements are adhered to.
APPROVED
Keywords: Modular Construction; Structural Dynamics; Operation Modal Analysis; Tuned Liquid Dampers; Multiple Vertically Distributed Tuned Liquid Dampers; Real Time Hybrid Testing; Data-Informed Modelling; Surrogate Modelling; High-Rise Buildings; Habitability Requirements; Occupant Comfort